Investigating the visible range photoresponse of an organic single-crystal analogue of the green fluorescent protein - Virole, Vishal; Dabke, Niteen; Verma, Sahil; Kumar, Ajay; Pandya, Rinu; Husale, Sudhir; Vanka, Kumar; Gonnade, Rajesh; Kanawade, Rajesh (Nanoscale, 2025)
The growing demand for lightweight, flexible, semi-transparent and low-cost photodetectors (PDs) in wearable electronics and optical communication systems has prompted studies to investigate organic materials as feasible alternatives to conventional inorganic PDs. However, modern organic PDs often face responsivity, detectivity, and photoresponse speed limitations, particularly in the visible range. Here, we present the photoresponse of an organic single-crystal analogue of the green fluorescent protein (GFP) chromophore photodetector, fabricated on a silicon nitride substrate. A significant increase in photocurrent was detected upon illumination with visible wavelengths (532 nm, 630 nm, and halogen light). A remarkably consistent and repeatable photoresponse was obtained during the ON and OFF illumination cycles. The device showed the dependence of photocurrent on the applied bias voltages. The measured photocurrent, responsivity, detectivity, rise time, decay time, noise equivalent power and external quantum efficiency are studied for different wavelengths. Strikingly, the fabricated device demonstrates excellent performance in the visible region compared to several conventional organic and inorganic PDs. The observed responsivity and detectivity values for the device are 98 mA W-1 and 7.94 x 108 Jones, respectively. Furthermore, the device also exhibits rapid photoresponse dynamics with a rise time of 180 ms and a decay time of 152 ms. The excellent photodetection features indicate that the single crystal GFP could serve as a versatile broadband material for future applications in optoelectronics.

Optimisation of metallic bismuth nanoparticle supported Pt-Bi(x%)/C hybrid electrocatalyst for cost effective and efficient hydrogen production in alkaline media - Dokhe, Revati; Ugale, Atul; Dube, Onkar; Varpe, Vaibhav; Galave, Chaitanya; Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Kumar, Ajay; Husale, Sudhir; Natu, Varun; Shevate, Rahul; et al. (International Journal of Hydrogen Energy, 2025)
The present study employed a simple mechanochemical method followed by 24-h ultrasonication to synthesize oxide-free metallic bismuth (Bi) nanoparticles. This was further used to synthesize a Pt-Bi(x%)/C (NC-x) hybrid electrocatalyst for the hydrogen evolution reaction in alkaline media. X-ray photoelectron spectroscopy and contact angle measurements reveal, Bi modifies the electronic structure and surface morphology of the Pt/C electrocatalyst, thus enhancing reaction kinetics and active site availability. The relative three-electrode study reveals that optimised NC-20 electrocatalyst reduces the overpotentials by 10.44 % and enhances the current density by 53 % compared to commercial Pt/C. The practical applicability of the NC-20 electrocatalyst was studied with the 13 cm2 single cell anion exchange membrane electrolyser. The catalyst demonstrates promising performance where the current density of NC-20//IrO2 relatively increases by 22.6 % compared to standard Pt/ C//IrO2, and shows continuous production and stable performance when monitored for 30 h.
Keywords: AEM; Bismuth nanoparticles; electrocatalyst; Full cell electrolysis; hydrogen evolution reaction; water electrolysis

Real-time estimation of blood oxygenation parameters from human foot sole during leg elevation: a preliminary study with diffuse reflectance spectroscopy - Kumar, Ajay; Lohchab, Viney; Pawar, Dnyandeo; Someshwar, Vimal; Mathe, Vikas; Husale, Sudhir; Kanawade, Rajesh (Optics and Laser Technology, 2025)
This study investigated the applicability of diffuse reflectance spectroscopy (DRS) for real-time and non-invasive measurement of blood oxygenation parameters (BOPs) such as reduced hemoglobin (RHb), oxyhemoglobin (HbO(2)), and oxygen saturation (SO2) from human foot sole during leg elevation. Seventeen (17) healthy male subjects aged between 21 to 39 years were included in this study. Diffuse reflectance spectra were recorded from measurement sites namely the 5th metatarsal, ball of great joint, calcaneum, and great toe of the human foot sole w.r.t. leg elevation angles such as 0(0), 15(0), 30(0), 45(0), and 60(0), respectively. The localized BOPs were derived from the recorded spectra. In addition, blood hemodynamic parameters (BHPs) such as heart rate (HR), SO2, perfusion index (PI), systolic blood pressure (SBP), and diastolic blood pressure (DBP) were also measured for each elevating angle. To study and assess the changes in BOPs and BHPs w.r.t. leg elevation, a One-way ANOVA test followed by a Tukey HSD post-hoc test was performed. We observed a statistically significant increase in RHb (p < 0.001) and a decrease in HbO(2) (p < 0.001) after 45 degrees of leg elevation, however, there was no statistically significant difference in SO2 (p = 0.74) and HR (p = 0.84) for each measurement site w.r.t. leg elevation, respectively. Furthermore, PI (p < 0.01), ankle SBP (p < 0.001) and DBP (p < 0.001) were decreased w.r.t. leg elevation. The obtained results are in agreement with the literature. The preliminary results suggest that DRS has the potential for real-time estimation of BOPs from the local sites of healthy human foot soles during leg elevation. Thus, it opens the possibility of DRS to monitor and evaluate the diagnosis and treatment of ischemia and edema during leg elevation of patients through BOPs measurement.
Keywords: diabetic foot ulcer; diffuse reflectance spectroscopy; Leg elevation; Oxygen saturation; Oxyhemoglobin; Reduced hemoglobin